Antifungal activity of nitroxoline against Candida auris isolates. (November 2021) - Fuchs, Frieder; Hof, Herbert; Hofmann, Sandra; Kurzai, Oliver; Meis, Jacques F.; Hamprecht, Axel
Abstract: Objectives: To investigate the in vitro activity of nitroxoline against a molecularly characterized collection of clinical Candida auris isolates. Methods: Thirty-five clinical isolates of C. auris from diverse sources representing all five different C. auris clades were included in the study. Nitroxoline activity was assessed using broth microdilution. Additionally, susceptibility testing by disc diffusion was assessed on RPMI-1640 and Müller–Hinton agar plates. Minimal inhibitory concentrations of the antifungals fluconazole, voriconazole, amphotericin B and anidulafungin were determined. Results: Nitroxoline MICs ranged from 0.125 to 1 mg/L (MIC50/90 0.25/0.5 mg/L). Compared with amphotericin B (MIC >1 mg/L in 4/35 isolates), anidulafungin (MIC >0.06 mg/L in 26/35 isolates) and fluconazole (MIC >4 mg/L in 31/35 isolates), in vitro activity of nitroxoline was high. Isolates belonging to clade I had marginally lower nitroxoline MICs (range 0.125–0.5 mg/L, mean MIC 0.375 mg/L) compared with clade III (range 0.5–1 mg/L, mean MIC 0.7 mg/L; p = 0.0094). The correlation of MIC and inhibition zones by disc diffusion was good when using RPMI-agar for disc diffusion, with a Pearson's correlation coefficient of –0.74 (95% CI –0.86 to –0.54). Conclusions: Nitroxoline has excellent in vitro activity against C. auris isolates, with MICs of 0.125–1 mg/L (for comparison, the EUCAST breakpoint for uncomplicated urinary tract infection with Escherichia coli is ≤ 16 mg/L). It is an approved, well-tolerated antimicrobial that achieves high urinary concentrations after oral administration and could be a useful treatment option in C. auris candiduria.